Eksplorasi Gaya Hidup Remaja dan Perilaku Seksual Berisiko (Multiple Partners): Studi Kualitatif di kota Samarinda - Dian Ardyanti; Joko Sapto Pramono; Eka Putri Rahayu; Indah Wardatul Jannah; Renatha Widyarisa Kristiono (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Sexual Infectious Infection (IMS) is a health condition caused by infections that spread through sexual activity. IMS can befall anyone and potentially have serious consequences, especially in reproductive organs. Adolescents who are undergoing a developmental phase with high curiosity about sexual behavior, are susceptible to unsafe sexual practices. The data recorded that 59% of women and 74% of men had sexual intercourse before marriage. This study aims to deeply analyze adolescents’ lifestyles as well as the driving factors of risky sexual behavior with multiple partners in Samarinda City. The approach used is qualitative with a case study design involving 7 informants. Data collection was conducted through in-depth interviews. Research results indicate that multiple partner sex behavior among Samarinda youth has been integrated into their lifestyle, which was formed through a process of normalization by the social environment. Adolescents view sexual activity from physical contact to intimate relationships with various partners as normal in the context of modern relationships.